TAKAFUL-GROWTH NEXUS BEFORE AND AFTER THE IMPLEMENTATION OF IFSA 2013: EMPIRICAL EVIDENCE FROM MALAYSIA - Kamarudin, Ainatul Aqilah; Duasa, Jarita; Kassim, Salina; Imon, Riasat Amin (International Journal of Islamic Banking and Finance Research, 2023)
The expanding Takaful industry, together with the remarkable economic development has drawn attention to explore the impact of Takaful on economic growth, especially in Malaysia as it has been retaining its position as the leader in Islamic finance as well as maintaining its position to be in top for the Global Islamic Economy Indicator (GIEI) Score for the 9th consecutive years. Although many challenges have been faced by Takaful successfully, there are still some issues that need to be improved especially in terms of the legal, supervisory, and institutional framework, and the directions for future research by focusing on statistical analysis and economic significance, and its primary objective to serve the society. Hence, this paper examines the association between the Malaysian Takaful sector and real economic growth pre and post-IFSA 2013 for the period of 2007 – 2019. This study employs both quantitative and qualitative analysis, in which Pearson Correlation Coefficient is adopted for the quantitative analysis, while an interview session with 5 experts is employed for the qualitative analysis. The quantitative findings show that Takaful is positively linked to real economic growth significantly pre-IFSA 2013 but insignificantly post-IFSA 2013, supporting the supply-leading hypothesis. Meanwhile, the qualitative findings suggest that IFSA 2013 does assist the Takaful sector to improve the real economic growth in Malaysia via its rules and regulation, and the Takaful industry has contributed its own humble quota to economic growth by creating jobs the society and adding value to both participants and businesses.JEL Classification Codes: G2, O4.